The effect of fluid overload on sleep apnoea severity in haemodialysis patients. Issue 4 (6th April 2017) - Lyons, Owen D.; Inami, Toru; Perger, Elisa; Yadollahi, Azadeh; Chan, Christopher T.; Bradley, T. Douglas
As in heart failure, obstructive and central sleep apnoea (OSA and CSA, respectively) are common in end-stage renal disease. Fluid overload characterises end-stage renal disease and heart failure, and in heart failure plays a role in the pathogenesis of OSA and CSA. We postulated that in end-stage renal disease patients, those with sleep apnoea would have greater fluid volume overload than those without. End-stage renal disease patients on thrice-weekly haemodialysis underwent overnight polysomnography on a nondialysis day to determine their apnoea–hypopnoea index (AHI). Extracellular fluid volume of the total body, neck, thorax and right leg were measured using bioelectrical impedance. 28 patients had an AHI ≥15 (sleep apnoea group; OSA:CSA 21:7) and 12 had an AHI <15 (no sleep apnoea group). Total body extracellular fluid volume was 2.6 L greater in the sleep apnoea group than in the no sleep apnoea group (p=0.006). Neck, thorax, and leg fluid volumes were also greater in the sleep apnoea than the no sleep apnoea group (p<0.05), despite no difference in body mass index (p=0.165). These findings support a role for fluid overload in the pathogenesis of both OSA and CSA in end-stage renal disease. Fluid overload plays a key role in the pathogenesis of OSA and CSA in end-stage renal disease http://ow.ly/zSZo308a8TP